HUBUNGAN LINGKUNGAN BELAJAR DENGAN PRESTASI BELAJAR SISWA TEKNIK GAMBAR BANGUNAN DI SMK NEGERI 4 SOLOK SELATAN - 118-125 . Andi (Universitas Negeri Padang, 2013)
The background of this study is the low student achievement in Teknik Gambar Bangunan subjects Menerapkan Dasar-dasar Gambar Teknik in SMK Negeri 4 Solok Selatan the academic year 2010/2011 as much as 42.86% and the academic year 2011/2012 a total of 37,5%. This study is correlational, which aims to reveal the relationship learning environment with academic achievement subjects Menerapkan Dasar-dasar Gambar Teknik, by hypothesis there is a correlation with academic achievement learning environment subjects Menerapkan Dasar-dasar Gambar Teknik students at SMK Negeri 4 Solok Selatan. The study population was all students in Teknik Gambar Bangunan as many as 38 people, with a total sampling techniques. The data were taken using a questionnaire Likert scale models to study environmental variables (X) and student achievement (Y) are from the semester exam subjects Menerapkan Dasar-dasar Gambar Teknik. Data analysis consisted of: (1) description of the data (2) testing requirements analysis and (3) test the hypothesis. Based on data analysis results that the correlation coefficient (r = 0.587) on the probability of 0.000 <0.05 Significant Alpha. The hypothesis is acceptable, there is a significant correlation between the learning environment with academic achievement. Key words : Lingkungan Belajar, Prestasi Belajar